Effectiveness Of PJBL And PBL Models On Numerative Literacy Based On Local Wisdom In Elementary Schools - Jannah, Ma'rifatul; Markhamah, Markhamah; Rahmawati, Fitri Puji (STKIP Singkawang, 2024)
The purpose of this study is to evaluate the impact of the PjBL (Project Based Learning) and PBL (Problem Based Learning) models on literacy and numeracy abilities based on local knowledge in elementary schools. In this work, a quantitative method and a quasi-experimental design are used. Students in fifth grade at SD Muhammadiyah 08 Cilacap made up the study population, and two classes—fifth grade students in class A using the PjBL model and fifth grade students in class B using the PBL model—made up the research sample. The tool being utilized is a test tool. Prior to usage, the instruments, which included multiple-choice and essay questions, underwent validity and reliability testing. Before managing and after administering therapy, the instrument was utilized for a posttest and pretest. This study aims to retest Nirmala's research (2023), which claims that Problem Based Learning has a greater average score of 82.68 for participant literacy and an average score of 81.00 for students' numerization. This finding appears to be in conflict with Ariyani and Prasetyo's research (2021), which reports a Particle eta Squared of 0.161 with a significance value of 0.079, indicating that the impact of Problem Based Learning and Problem Sol The usefulness of the PjBL model with the PBL model on locally based numeracy and literacy skills in elementary schools is examined in this study. The independent sample t-test and the paired sample t-test were used to test hypotheses. Before using the PjBL learning paradigm with PBL based on local wisdom, the typical daily test score for classes 5A and 5B was 55.95 and 59.7, respectively. The average score after managing the implementation of the PBL model is 77.7 in class 5A and 91.8 in class 5B, compared to 62, 15, and 66.6 after handling the implementation of the PjBL model in class 5A. The findings indicated that the PBL model was superior than the PjBL model in terms of improving reading and numeracy abilities based on local wisdom in elementary schools.